The Bright Side of Tax Evasion - Wladislaw Mill; Cornelius Schneider (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates whether tax evasion can be beneficial for an optimal income tax schedule. Past theoretical discussions have presented mixed outcomes as to whether allowing taxpayers to opt into uncertainty could indeed enhance overall tax revenues. In this study, we conducted an original real effort experiment in an online labor market with almost 1,000 participants to test this hypothesis empirically. Our findings show significant positive labor supply responses to the opportunity to evade (increased labor supply by 37%). More importantly, the expected tax revenue significantly and substantially increased by up to more than 50%. As an example, our data suggests that a 40% tax rate with complete enforcement could be replaced with a 28% tax rate with the option of tax evasion, without any loss in tax revenue. Strikingly, this effect persists when comparing effective tax rates: Lowering effective tax rates through probabilistic enforcement (the opportunity to evade) is more efficient than simply lowering statutory tax rates. Our findings suggest that the opportunity for tax evasion can increase tax revenues beyond what a corresponding decrease in nominal rates would achieve. For welfare analyses, this highlights the importance of not only considering the elasticity of taxable income (ETI) but total earned income elasticities.
Keywords: H21; H24; H26; J22; C91; 330; tax evasion; tax revenues; labor supply; optimal taxation; experiment